Efektivitas Pendekatan Pembelajaran Berdiferensiasi untuk Meningkatkan Literasi Numerasi Siswa - Suryatama, Handika; Rozaq, Ramadhan Rifana; Purwanti; Siswanto, Deny Hadi (Prodi PGMI STAI Sabili Bandung, 2024)
This study aims to determine the effectiveness of the differentiated learning approach to improve students' numeracy literacy. The type of research used is a quasi-experimental study, with 60 students as research subjects consisting of 30 students in class Va and 30 students in class Vb Madrasah Btidaiyah Macanmati. Data were collected through tests, observations, and interviews. Data analysis techniques include validity and reliability tests for instrument tests and normality tests, homogeneity tests, and t-tests to determine the effectiveness of the differentiated approach to improve students' numeracy literacy, as well as Gain tests to determine the type of increase. The results of the study showed that the data were normally distributed and homogeneous, so they were continued with a t-test. The results of the t-test were 0.000 <0.05, meaning that the differentiated learning approach was effective in improving students' numeracy literacy with an increase in the Gain test of 0.72 in the high category